(untitled) (Heritage, 2021)
In this paper we discussed about the occult ritual present in Bosnian culture, specifically linked to the tradition of Bosnian muslims. In the first part of the paper we explored the specific bordering segments of magic and religion relying on the theories of famous sociologists/anthropologists. The second part of the paper primarily consists of recent studies on the topic of lead casting in Bosnian cultural context. The third part has been dedicated to the specific anthropological research of lead casting tradition in two towns in Central Bosnia. We concluded that this occult tradition has its background in the pagan rituals but it in the actual case it blends with elements of islamic tradition primarily suported with verses from the Quran